New early eocene mammalian fauna from western Patagonia - Tejedor, Marcelo Fabian; Goin, Francisco Javier; Gelfo, Javier Nicolás; López, Guillermo Marcos; Bond, Mariano; Carlini, Alfredo Armando; Scillato, Gustavo Juan; Woodburne, Michael O.; Chornogubsky Clerici, Laura; Aragon, Eugenio; Reguero, Marcelo Alfredo; Czaplewski, Nicolas J.; et al.
Two new fossil mammal localities from the Paleogene of central-western Patagonia are preliminarily described as the basis for a new possible biochronological unit for the early Eocene of Patagonia, correlated as being between two conventional SALMAs, the Riochican (older) and the Vacan subage of the Casamayoran SALMA. The mammal-bearing strata belong to the Middle Chubut River Volcanic-Pyroclastic Complex (northwestern Chubut Province, Argentina), of Paleocene-Eocene age. This complex includes a variety of volcaniclastic, intrusive, pyroclastic, and extrusive rocks deposited after the K-T boundary. Geochronological data taken from nearby volcanic deposits that underlie and overlie the mammal-bearing levels indicate that both faunas are of late early Eocene age (Ypresian-Lutetian boundary). In addition to more than 50 species of mammals, including marsupials, ungulates, and xenarthrans, two lower molars are the oldest evidence of bats in South America. Paleobotanical and palynological evidence from inferred contemporary localities nearby indicate subtropical environments characterized by warm and probably moderately humid climate. Remarkably, this new fauna is tentatively correlated with Eocene mammals from the La Meseta Formation in the Antarctic Peninsula. We conclude that the two localities mentioned above are part of a possible new biochronological unit, but the formal proposal of a new SALMA awaits completion of taxonomic analysis of the materials reported upon here. If the La Meseta fauna is correlated biochronologically to western Patagonia, this also suggests a continental extension of the biogeographic Weddelian Province as far north as centralwestern Patagonia. Fil: Tejedor, Marcelo Fabian. Division of Vertebrate Zoology (Mammalogy), American Museum of Natural History; Estados Unidos Fil: Goin, Francisco Javier. División Paleontología de Vertebrados, Facultad de Ciencias Naturales y Museo de La Plata; Argentina Fil: Gelfo, Javier Nicolás. División Paleontología de Vertebrados, Facultad de Ciencias ...